How are mergers beneficial : a look at operating efficiencies, taxes and market power as sources of synergies in Singapore. - Tan, Kian Tiong. (2010)
Evidence in literature today regarding the underlying sources of synergies for mergers in Singapore is non-substantial. Past research indicates that these synergies are a result of tax shields, productive efficiencies and market power. In a sample consisting of 48 mergers, we estimate average gains to be 9.93% of the combined equity value of the merging firms. The use of actual data allows us to segregate these synergies into underlying operating and financial synergies. We find out that tax savings contribute only 0.29% in additional value, while operating synergies is at 9.63%. Operating synergies are significantly higher in focused mergers, with tax savings accounting for a significant portion of gains in diversifying mergers. Revenue increases/cost savings are mainly responsible towards operating synergy gains. Overall, evidence shows that merger synergies arise mainly from market power and productive efficiency rather than tax shields.